A rare presentation of giant teratoma in the mediastinum of an adolescent – a case report and treatment outcome - Anderko, Iwona; Sosnowska-Sienkiewicz, Patrycja; Szot, Mateusz; Haraś, Paulina; Mańkowski, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Mediastinal teratoma is an unusual germ cell tumor, accounts for 1–5% of all mediastinal tumors and is the most common type of the mediastinal germ cell tumor. While mature mediastinal teratomas are infrequent, their discovery is often incidental. This case presents a 16-year-old boy with left-sided chest pain, dry cough, and decreased exercise tolerance persisting for several weeks. Imaging revealed a large mediastinal mass displacing cardiac structures and compressing the left lung. A biopsy indicated a mixed germ cell tumor, predominantly an immature teratoma with a minor yolk sac tumor component. The patient received four cycles of neoadjuvant chemotherapy, followed by complete surgical resection, with histopathology confirming a benign mature teratoma. Two months post-surgery, he developed myelodysplastic syndrome, likely related to chemotherapy, and underwent an allogeneic stem cell transplant. This case underscores the importance of multidisciplinary care and vigilant follow-up in managing large mediastinal germ cell tumors in adolescents.